In-situ graphene enhanced copper wire: A novel electrical material with simultaneously high electrical conductivity and high strength. (January 2022) - Gao, Zhaoshun; Zuo, Tingting; Wang, Meng; Zhang, Ling; Da, Bo; Ru, Yadong; Xue, Jiangli; Wu, Yue; Han, Li; Xiao, Liye
Abstract: Copper-based materials with high electrical conductivity and high strength are strongly desired in energy and electric power fields. Unfortunately, it's almost impossible to obtain scalable and facile copper-based materials with the combined improvement of electrical conductivity and strength through traditional means. Here, by in-situ grown high quality graphene in copper through vacuum hot-press sintering the Cu powder and non-toxic, cheap liquid paraffin, high electrical conductivity and high strength are easily realized. Through further elaborate structure design and morphology control of graphene by altering the copper powder size, the liquid paraffin content and the sintering process parameters, the performance is improved. The uniformly-distributed 3D graphene plays a vital role, which acts as an electron transport channel and strengthens the matrix by grain refinement, dislocation strengthening and load transfer mechanisms. As a result, the cold drawn Cu/Graphene composite wire exhibits high electrical conductivity of 94.85% IACS and high tensile strength of 516 MPa, together with good softening resistance. This work provides a low cost and high-efficiency way to prepare high-performance graphene reinforced Cu matrix composite, and opens a new window for large-scale production of high-performance Cu/Graphene composites with different shapes. Graphical abstract: Image 1 Highlights: High-performance Cu/Gr composite is simply prepared by vacuum hot-press sintering. The in-situ grown Gr is affected by raw materials and sintering process. The cold drawn Cu/Gr wires possess high strength and high electrical conductivity. 3D Gr induces grain refinement, dislocation and load transfer strengthening.